PENDAMPINGAN PENGUKURAN VOLUME PEKERJAAN TROTOAR - Endah Atika; Galih Saputra (BESIRU : Jurnal Pengabdian Masyarakat, 2026)
Sidewalk construction is an essential component of urban infrastructure development that supports pedestrian safety, comfort, and accessibility. However, in practice, discrepancies are often found between the installed work volumes and the planned calculations, mainly due to limited technical understanding, insufficient accuracy in field measurements, and a lack of technical assistance. These conditions may lead to quality issues, cost overruns, and disputes during project implementation. This Community Service activity aims to provide technical assistance to partners in measuring and verifying sidewalk construction volumes so that the execution process becomes more accurate, transparent, and compliant with applicable technical standards. The implementation methods include delivering basic material on construction volume measurement, conducting hands-on field measurement practices, and facilitating discussions and evaluations of the measurement results in a participatory manner. Through this activity, partners are expected to improve their understanding and skills in properly measuring sidewalk construction volumes, thereby minimizing calculation errors and enhancing the quality and sustainability of construction work control.